Good Living as a Living Law - Gallegos Anda, Carlos E. (The Australian Journal of Indigenous Education, 2017)
In 2008, Ecuador reformed its Constitution after a prolonged period of economic, social and political crises. The momentary rupturing of power structures, that had limited political participation to small clusters of elites, opened participatory spaces for historically marginalised social groups to engage in the process of constitutional drafting. As a result of this unprecedented political shift in participation and inclusiveness, alternative notions of cultural, social and economic rights surfaced. This progressive constitutionalism is thus a novel attempt at overcoming legal formalism in favour of a Living Law, a law that embraces the contextual settings where it will be applied by scrutinising the historic power structures that have moulded it. Good Living as a legal principle underlines the enactment of a Living Law.